EFFECTS OF HANDPHONE’S ELECTROMAGNETIC WAVE EXPOSURE ON SEMINIFEROUS TUBULES - Victorya, Roseane Maria (Majority, 2015)
Abstract Mobile phone (handphone) user in Indonesia increase every year. The user have to notice about the side effects of handphone utilization againts human’s health. The side effect may be as user’s body exposure againts the electromagnetic wave which is used as data transfer media. Reproductive system disorders caused by electromagnetic wave could be happen, especially for the male user who places the handphone in their trousers’ pocket frequently . It has been reported that electromagnetic wave exposure causing tissue damage, interfere spermatogenesis proccess, affect Sertolli cells and Leydig cells on animals. The most probable mechanism causing effects between electromagnetic wave againts human’s health is the imbalance of free radicals in biologic system. The imbalance between Reactive Oxygen Species (ROS) and protective antioxidants causing an oxidative stress. A big number of ROS causing patologic responds that ends with the cell and tissue damage. The ROS causing seminiferous tubules degeneration. Keywords: electromagnetic wave, handphone, oxidative stress, seminiferous tubules Abstrak Pengguna telepon seluler (handphone) di Indonesia meningkat setiap tahunnya dan membuat para pengguna harus memperhatikan efek samping penggunaan handphone terhadap kesehatan manusia. Efek samping tersebut dapat berupa paparan tubuh pengguna handphone terhadap gelombang elektromagnetik yang digunakan sebagai media transfer data. Gangguan pada sistem reproduksi yang disebabkan oleh paparan gelombang elektromagnetik dapat terjadi, terutama untuk pengguna handphone pria yang sering menyimpan handphone di dalam saku celana. Telah dilaporkan bahwa paparan gelombang elektromagnetik dapat menyebabkan kerusakan dalam jaringan, mengganggu proses spermatogenesis, merusak sel Sertoli dan sel Leydig pada hewan percobaan. Mekanisme yang paling mungkin menyebabkan pengaruh antara gelombang elektromagnetik terhadap kesehatan adalah adanya perubahan keseimbangan kadar radikal bebas dalam sistem biologik. Ketidakseimbangan antara ROS dan antioksidan protektif dapat menyebabkan stres oksidatif. ROS dalam jumlah besar dapat menyebabkan respon patologis yang berakhir dengan kerusakan sel dan jaringan. ROS menyebabkan degenerasi pada tubulus seminiferus. Kata kunci: gelombang elektromagnetik, handphone, stres oksidatif, tubulus seminiferus